2021
DOI: 10.18502/ijaai.v20i1.5419
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Severe Angioedema without Exogenous Hormone Exposure

Abstract: Hereditary angioedema (HAE) is characterized by recurrent attacks of skin and mucosal swelling in any part of the body including the digestive and respiratory tract which generally improve spontaneously within 12-72 hours. The underlying mechanism in HAE is related to bradykinin dysregulation which causes these attacks not to respond to common treatment strategies including epinephrine or corticosteroid. There are several types of HAE with different etiology but with the same clinical picture. Type 1 is due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…This pattern aligns with prior studies, which have demonstrated that HAE III type primarily develops in females, with initial symptoms typically emerging during adolescence [56]. One compelling link to this phenomenon is that mutations of the F12 gene can be associated with increased sensitivity of the F12 protein to estrogen-like elements, leading to elevated bradykinin production and the development of soft tissue edema [57,58]. The underlying reason of this phenomenon can be that estrogens can interact with most stages of the complex bradykinin cascade, and the hormonal in uence can be mediated either through classical nuclear-genomic actions or non-genomic effects at the membrane level or by affecting various kinases in the cytoplasm [59].…”
Section: Discussionsupporting
confidence: 87%
“…This pattern aligns with prior studies, which have demonstrated that HAE III type primarily develops in females, with initial symptoms typically emerging during adolescence [56]. One compelling link to this phenomenon is that mutations of the F12 gene can be associated with increased sensitivity of the F12 protein to estrogen-like elements, leading to elevated bradykinin production and the development of soft tissue edema [57,58]. The underlying reason of this phenomenon can be that estrogens can interact with most stages of the complex bradykinin cascade, and the hormonal in uence can be mediated either through classical nuclear-genomic actions or non-genomic effects at the membrane level or by affecting various kinases in the cytoplasm [59].…”
Section: Discussionsupporting
confidence: 87%